Verification and Modeling of the Maritime Channel for Maritime Communications and Navigation Networks - Raulefs, Ronald; Bellido-Manganell, Miguel A.; Dammann, Armin; Walter, Michael; Wang, Wei (Frontiers in Marine Science, 2023)
This paper describes a geometric stochastic channel model that can be used to analyze maritime communication and navigation services between moving ships using the C-band or sub-6 GHz spectrum, which is currently the focus of emerging 5G networks on land. The channel model is verified by channel measurements on the sea and the land which have been analyzed and integrated into a software tool that is provided along with this publication. The key difference between channel models for maritime and land-based services is the constantly changing sea surface. This results in varying reflection conditions such as changing reflectors and scatterer on the sea surface. In addition, the motion conditions of the transmitter and receiver on the ship change in all three dimensions depending on the sea state. The collected data of several measurement campaigns in different areas were used to analyze the propagation conditions over the sea by varying the sea surface roughness, the antenna heights, and the used bandwidths used, as well as the additional propagation conditions over the nearby land. The influence of the changing antenna height on the ship due to the sea conditions affects the reflection and scattering conditions. Currently reliable, high-data rate and broadband marine communication systems are currently investigated Therefore, the measurement bandwidth of 120 is used to derive the propagation model that also provides absolute timing information and can be used for a time-based ranging or positioning system.